SISTEM INFORMASI NILAI BERBASIS SMS - Umti Mardiyati (Universitas Amikom Purwokerto, 2010)
Application of information lechnology based on SMS (Short Message Service) is very helpfulin meeting the needs for data processing and presentarion of information faster and moreinteroctive as well as distributing information quickly, accurate, relevant and timely becausein the process of it without knowing the limits of time and ,space. Moreover, supported by therelatively cheap cost and eqsy usage.